Roundtable Discussion on Economic Development, Georgia State, GA, December 11, 2006 - Wolfowitz, Paul; Young, Andrew (2016)
Paul Wolfowitz, President of the World Bank, and Ambassador Andrew Young engaged in a roundtable discussion on economic development, moderated by Dean Bahl of Georgia State. Wolfowitz has made Africa the first priority of the Bank. There is really a chance for Africa to turn the corner. It’s going to have to start with the best performers, doing what the so-called Tigers did in East Asia, showing the way for other countries. Young said you can make more money honestly in a growing economy, than you can steal in a dying economy. Wolfowitz gave examples of the turnaround in Africa. Africa needs an environment where foreign investment support and local domestic investment is even more important.